The Dynamics of Facilities, Learning Environment, and Student Activities at SDN 106833 Wonosari Village, Tanjung Morawa District - Saharani, Noni Arnisa; Harahap, Rahma Hayati (Talenta Publisher, 2024)
Education is important in equipping individuals with knowledge and skills that help them adjust to social life. School quality has a strong impact on student output. Schools with good and complete building conditions can improve schools to meet health and safety standards, which can increase student quality. Substandard physical environment is strongly associated with other behavioral problems with students such as lower student attendance leading to lower student scores. the purpose of this study was written to know the facilities and infrastructure, the school's efforts in implementing learning at SD Negeri 106833 Wonosari. The method used in is called qualitative. This paper focuses on learning tools that can help students maintain their education. This study investigated the relationship between school physical environment, learning tools, and student learning outcomes. The findings revealed the physical condition of schools and the availability of learning tools have a significant impact on student learning outcomes.